Aksesibilitas Informasi, Sistem Pengendalian Internal, Pelatihan, dan Akuntabilitas Pengelolaan Dana Desa: Peran Teknologi Informasi - Shafira, Alma Yumna; Utami, Evy Rahman (E-Jurnal Akuntansi, 2021)
This research aims to examine the effect of village information accessibility, internal control systems, village apparatus training on the accountability of village fund management with the use of information technology as a moderating variable. The sample was selected using the proportional stratified random sampling method. Analysis technique uses multiple linear regression and linear regression with the absolute different value test. The results of this research showed that the accessibility of village information and the internal control system have a positive effect on the accountability of village fund management, the use of information technology reinforces the positive influence of the internal control system on the accountability of village fund management. However, training for village officials has no effect on the accountability of village fund management. Keywords: Accessibility; Internal Control System; Training; The Information Technology; Accountability; Village Fund.